Penerapan Sistem Informasi Akutansi Pada Toko Panca Jaya Menggunakan Integrated System - B.Bus, M.Com, Michael Andiranto T, Rinabi Tanamal, (PROCEEDING IC-ITECHS 2014, 2014)
Accounting information system is a very important part for Panca Jaya store. PancaJaya store is a retail store, which using a manual system, so they may fine difficulties in stock checking, purchases, sales, and accounting. Currently there are many Accounting Information System which can facilitate the process of store operations with a computer system. Integrated system is one accounting information system software that has been used in a variety of stores. This software provides some basic modules needed for the store implementation. Because of that Integrated System, Panca Jaya performed in order to answer the needs of the store and assist in conducting stock checking, purchases , sales and accounting also in store.